2015
DOI: 10.1021/jp512567h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Photocatalytic Suzuki–Miyaura Coupling Reaction on Mott–Schottky-type Pd/SiC Catalyst

Abstract: The Mott−Schottky heterojunction in Pd/SiC can continuously transfer photogenerated electrons to Pd nanoparticles and leave holes in SiC under irradiation. The electrons in Pd particles and holes in SiC played different roles in the photocatalytic Suzuki−Miyaura coupling reaction, respectively, for cleaving the C−Br or C−I bond in benzene halides and the C−B bond in phenylboronic acids. Therefore, the intrinsic activity of Pd was dramatically enhanced when employing SiC-supported Pd nanoparticles as the photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 24 publications
(50 reference statements)
3
95
0
1
Order By: Relevance
“…Recently, high specific surface area β‐SiC has been supposed as a potential support alternatives to carbon materials due to its stable chemical property, high mechanical strength and good thermal conductivity . In the previous researches, we found that the electron transfer occurred between metals and SiC caused by Mott‐Schottky effect, which can significantly tune the activity and selectivity of SiC‐supported metallic catalysts …”
Section: Background and Originality Contentmentioning
confidence: 96%
“…Recently, high specific surface area β‐SiC has been supposed as a potential support alternatives to carbon materials due to its stable chemical property, high mechanical strength and good thermal conductivity . In the previous researches, we found that the electron transfer occurred between metals and SiC caused by Mott‐Schottky effect, which can significantly tune the activity and selectivity of SiC‐supported metallic catalysts …”
Section: Background and Originality Contentmentioning
confidence: 96%
“…[5][6][7]15,20] The supported Pd catalysts can exist stably without any surfactants and therefore effectively circumvent the reduction of catalytic activity induced by the aggregation and steric hinderance of surfactants. [5][6][7]15,20] Most of Suzuki coupling reactions takes place at thermal heating conditions, which consumes a relatively large amount of energy. To realize green Suzuki coupling reactions, Pd are integrated with solar active materials which absorb light to provide energy for reaction.…”
Section: Graphitic Carbon Nitride (G-c 3 N 4 ) Supported Palladium Spmentioning
confidence: 99%
“…[10][11][12][13][14][15] Pd nanoparticles have been loaded on SiC particles and achieved photocatalytic Suzuki coupling reaction. [20] Similar to other two-dimensional materials, [21,22] g-C 3 N 4 has been widely studied in photocatalytic hydrogen evolution, [23][24][25] CO 2 reduction [26] and N 2 fixation [27] owing to its suitable energy band structure, low cost, and facile synthesis. Moreover, compared with SiC, the abundant nitrogen atoms and six-fold cavities formed by nitrogen atoms can bind Pd nanoparticles or Pd atoms very strongly, [6,23,25] which effectively inhibits the aggregation of Pd nanoparticles and thereby increases the stability.…”
Section: Graphitic Carbon Nitride (G-c 3 N 4 ) Supported Palladium Spmentioning
confidence: 99%
“…Another Mott‐Schottky type photocatalyst (Pd/SiC) has also been developed for photocatalyzed Suzuki C−C cross‐coupling reaction under visible light irradiation at room temperature. Guo et al . have demonstrated that the Mott‐Schottky type Pd/SiC photocatalyst showed a high activity (TOF of 1053 h −1 and selectivity of 100 %) with good stability and recyclability under visible light irradiation for 80 min at 30 °C in the coupling of iodobenzene and phenylboronic acid.…”
Section: Pd Supported Semiconductor Photocatalysts For Visible‐light mentioning
confidence: 99%